Sharing economy and applications: Business and marketing perspective - Pınarbaşı, Fatih (IGI Global, 2019)
Sharing economy has emerged as influential economic model in the last decades. A considerable literature has grown up around the sub-themes of sharing economy including business-related, system-related, and other context-related studies. Examining a general phenomenon in a limited scope is a strategy for specific perspective and conclusions. Therefore, examining sharing economy phenomenon in a business and marketing perspective can be useful for business related viewpoint. The study is composed of three parts and begins with a theorotical review of conceptual background. It will then go on to three level structures for this study, including consumer level, business and brand level, and system levels. The remaining part includes context-based studies about level structure. After reviewing topics in contexts, there are presented selected studies about related contexts. The study aims to research sharing economy in a general view and review business- and marketingrelated topics and studies.
Keywords: Economy; Business; Marketing